OPTIMALISASI AKTIVITAS DAN HASIL BELAJAR IPA PESERTA DIDIK MELALUI MODEL PROBLEM BASED LEARNING BERBANTUAN MEDIA AUDIO VISUAL - Sultanni, Mahdinian Sri; Hariyono, Eko; Maharani, Tety Dwi (Universitas Muhammadiyah Tapanuli Selatan, 2024)
Learning activities are placed as an influence on developing potential, self-control, spiritual strength and the skills needed to benefit fellow individuals. Learning strategies require collaboration with students' learning styles to support exploring their potential. The low science learning outcomes obtained during observations were caused by the use of learning models that were not based on students' learning styles. The aim of this research is to optimize students' science learning activities and outcomes through the Problem Based Learning model assisted by audio-visual media. This type of research is included in the Classroom Action Research (PTK) category with the subject being students in class VII C of SMP Negeri 2 Lamongan for the 2023/2024 academic year. Data collection techniques use observation, tests and documentation. The results of the research showed that in cycle 1 the percentage of students' learning activities was 74% and learning outcomes were 75%. The reflection stage obtained in cycle 1 became a provision in perfecting learning activities in cycle 2, so that the percentage obtained from cycle 2 regarding students' learning activities increased to 92% and student learning outcomes are 89%. It can be seen from the percentage obtained in cycle 2 that it has reached the classical limit set by the researcher. This shows that science learning using the Problem Based Learning learning model assisted by audio-visual media has a positive impact in optimizing students' activities and learning outcomes.